Disappearance of recurrent intra-abdominal extrahepatic hydatid cyst following oral albendazole administration. - Michail, O P; Georgiou, C; Michail, P O; Felekouras, E; Karavokyros, I; Marinos, G; Giannopoulos, A; Griniatsos, J (West Indian Med J, 2007)
A 44-year old male patient with a past medical history of a complete surgical excision of pelvic hydatid cyst two years previously presented with constant pelvic floor pain and plasma IgG anti-echinococcal antibody titres of 14.27 U/mL. Based on that and the imaging findings of abdominal ultrasound (US), Computed Tomography (CT) and Magnetic Resonance (MR) the diagnosis of a recurrent retrorectal pelvic hydatid cyst was made. Three courses of oral albendazole treatment were administered and sixteen weeks later, the patient was admitted for a planned elective operation. At that time, a new CT scan revealed disappearance of the cyst, while the serological tests showed a decrease in the IgG anti-echinococcal antibody titres to 0. 71 U/mL. Four different species of the Echinococcus tapeworm can produce infection in humans. E granulosus and E multilocularis are the most common, causing cystic and alveolar echinococcosis respectively, while E vogeli and E oligarthrus, have only rarely been associated with human infection. Although surgical resection remains the treatment of choice for hydatid disease, the present case could suggest that especially in cases of recurrent intraabdominal extrahepatic hydatid cyst, treatment with albendazole may lead to disappearance of the recurrent cyst therefore, should constitute a first line therapeutic option prior to any planned reoperation.
Keywords: Abdomen; Administration, Oral; Adult; Albendazole; Animals; Antiprotozoal Agents; Echinococcosis, Hepatic; Humans; Male; Pelvic Pain; Recurrence